Analysis and Computer Simulation of Biopore Tubes Made of Concrete Foam Reinforced by Durian Skin Fiber - Bustami Syam; Maraghi Muttaqin; Fakhrur Rozy; Malvin Setiawan; M. Fauzi; Fadly Ahmad Kurniawan (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
This research was conducted to utilize durian skin waste into useful materials by maximizing its utilization to solve environmental problems. The idea is to process the fibers so that they can be used as composite reinforcement material. Here, the durian fibers are used as fillers for foam concrete. The so-called concrete foam composite is designed and manufactured to produce tubes utilized for biopore systems. Biopore tube materials were tested and the tubes are also subjected to field tests to check their response subjected to static loading. A series of computer simulations are conducted. Results are compared with other biopore tubes (PVC and concrete). The simulation results show that the concentration of stresses is obviously seen around the hole located in the middle and upper section of the tubes. However, at those critical points in the tubes, the stresses are of smaller than that of the strength of the tubes. We conclude that biopore tubes with 16 holes in total provided on the tube wall are still feasible to be produced.